High Density Short Rotation Poplars for Pulp and Paper Manufacture - Rai, A. K.; Sharma, K. K.; Sharma, Y. K. (Indian Forester, 1991)
Thee paper presents the results on high density plantation of poplars and their avaliability for pulp and paper manufacture as a short rotation crop. The reaults of the study at the age of two years indicated that total air, dried bole-biomass was higher (i.e. 24.4 t/ha) In case of Populus × euramericana '72/58' as compared to Populus deltoldes 'G-3' (17.5 t/ha). At the age ot three years, P. deltoldes 'G-3' had taken the lead and contributed the highest total bole air dried biomass i.e. 52.6 t/ha aa compared to 37.8 t/ha by P. × euramericana '72/58'. At the age of three years for both P. deltoldes '0-3' and P. × euramericana '72/58' the total air dried above ground biomass (bole end branches) was of the order of 55.5 and 45.5 t/ha, reapectlvely. The evaluation of pulping and papermaking qualities on pilot acale, using the woody material of P. × euramericana '72/58' Ind P. deltoldes '0-3' indlclted that a 50 : 50 mixture of 2 Ind 3 years ega wood with bark is suitable for producing wrapping paper from both the species. The laboratory experlments showed that the same mixture with bark is also suitable for producing writing and printing papers.